Association between sarcopenia and osteoporosis: the cross-sectional study from NHANES 1999–2020 and a bi-directions Mendelian randomization study - Zhu, Yuan; Zeng, Qingyue; Shi, Yi; Qin, Yu; Liu, Simin; Yang, Yuhao; Qiu, Yu; Pan, Mengjia; An, Zhenmei; Li, Shuangqing (Frontiers in Endocrinology, 2024)
Background Osteoporosis (OP) and sarcopenia are prevalent musculoskeletal conditions among the elderly. Nevertheless, the causal relationship between sarcopenia and OP remains a subject of controversy and uncertainty. In this study, we employed cross-sectional analysis and Mendelian randomization (MR) to investigate the intricate relationship between sarcopenia and OP. Methods The cross-sectional study utilized data from the National Health and Nutrition Examination Survey (NHANES) spanning 1999-2020, which involved in 116,876 participants. It assessed the correlation between sarcopenia, osteoporosis (OP), and bone mineral density (BMD) using Chi-square tests, T-tests, and a multiple logistic regression model. Additionally, we conducted Mendelian randomization (MR) analysis to investigate the causal effects of sarcopenia-related characteristics (ALM) on OP. We employed IVW, sensitivity analysis, heterogeneity testing, and other methods for MR. The ALM data was sourced from the UK Biobank (n=450,243), while the aggregated data on OP was obtained from GWAS statistics (n=53,236). Results In this cross-sectional analysis, we observed that in the multivariate logistic regression model, without adjusting for any variables, OP emerged as a risk factor for sarcopenia [OR 95% CI = 1.90 (1.13-3.18), P = 0.02]. Following adjustments for gender, age, BMI, and biochemical variables, OP retained its status as a risk factor for sarcopenia [OR 95% CI = 3.54 (1.91-6.54), P < 0.001]. Moreover, after accounting for all variables, OP emerged as an independent risk factor for sarcopenia [OR 95% CI = 4.57 (1.47-14.22), P = 0.01].In the MR analysis, we uncovered that femoral neck BMD (FN BMD), lumbar spine BMD (LS BMD), and forearm bone mineral density (FA BMD) exerted a direct causal influence on ALM [FA BMD: OR 95% CI = 1.028 (1.008, 1.049), p = 0.006; FN BMD: OR (95% CI) = 1.131 (1.092, 1.170), p = 3.18E-12; LS BMD: OR (95% CI) = 1.080 (1.062, 1.098), p = 2.86E-19]. Conclusion Our study has revealed a positive correlation between OP and the prevalence of sarcopenia. It suggests a potentially robust causal relationship between OP and sarcopenia. Notably, OP appears to be associated with a higher likelihood of losing ALM, and a significant loss of ALM may contribute to a decline in LS BMD.